Analisis Pengukuran Sharia Compliance dalam Pelaksanaan Good Corporate Governance Bank Syariah di Indonesia - Dedhi Ana Mey Saramawati; Ahmad Tarmizi Lubis (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2014)
This research is an exploratory study aimed to measure and assess sharia compliance inthe framework of implementation of Good Corporate Governance in Sharia BankingIndonesia based an indicators used. That the results of this study can be compared byresearch of other similar, used indicators is an indicator that has been adapted from twoearlier studies i.e Thea Vinnicombe (2010) with title “ AAOIFI Reporting Standards :Measuring Compliance” and Sepky Mardian (2011) “ Study Exploration of DisclosureApplication of Sharia Compliance in Islamic Banks”. This research using 4 (four) indicators are : (i) Sharia Supervisory Board, which is a key player in Sharia Banking, (ii) Murabaha, is one contract that dominates Sharia Banking assets, (iii) zakah, an appraiser social function of Sharia Banks, and (iv) Mudharaba, which is a profit loss sharing contract with the identity of Sharia Banks. This research uses content analysis methodology, namely to make the sets specific text as the unit of analysis to figure out the purpose of the disclosure to be assessed in accordance with sharia compliance. Theannual reports are used GCG Implementation report and Financial Statement period2011. The results of this research indicate that level of Sharia Compliance Sharia Banking in Indonesia has been quite adequate with a percentage exceeding 50%, and in general, the tenth of Sharia Banking has been disclosed sharia compliance in the implementation of GCG.